2015
DOI: 10.1080/08927014.2015.1067887
|View full text |Cite
|
Sign up to set email alerts
|

In vitrophenotypic differentiation towards commensal and pathogenic oral biofilms

Abstract: Commensal oral biofilms, defined by the absence of pathology-related phenotypes, are ubiquitously present. In contrast to pathological biofilms commensal biofilms are rarely studied. Here, the effect of the initial inoculum and subsequent growth conditions on in vitro oral biofilms was studied. Biofilms were inoculated with saliva and grown anaerobically for up to 21 days in McBain medium with or without fetal calf serum (FCS) or sucrose. Pathology-related phenotypes were quantified and the community compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 35 publications
(38 reference statements)
8
67
1
Order By: Relevance
“…These results corroborate prior studies demonstrating the antifungal activity of P. aeruginosa 313536, and the frequent co-isolation of S. epidermidis and C. albicans in oral polymicrobial infections133137. Fungi are also part of the healthy oral microbiota, supporting the growth of oral anaerobes and increasing the resilience of the consortium2838. Indeed, we also found a remarkably higher relative abundance, but not differing species, of anaerobes in ETTs harbouring Candida versus those that did not.…”
Section: Discussionsupporting
confidence: 91%
“…These results corroborate prior studies demonstrating the antifungal activity of P. aeruginosa 313536, and the frequent co-isolation of S. epidermidis and C. albicans in oral polymicrobial infections133137. Fungi are also part of the healthy oral microbiota, supporting the growth of oral anaerobes and increasing the resilience of the consortium2838. Indeed, we also found a remarkably higher relative abundance, but not differing species, of anaerobes in ETTs harbouring Candida versus those that did not.…”
Section: Discussionsupporting
confidence: 91%
“…This seemed to be in contrast with earlier findings, where the presence of PHS decreased the number of viable S. mutans from a 24-h biofilm by 80% [Cukkemane et al, 2015]. This may be explained by the presence of a complex EPS produced by multiple bacterial species, which could render biofilms more persistent than those build by a monoculture, as postulated elsewhere [Janus et al, 2015;Martin et al, 2016;Payne and Boles, 2016].…”
contrasting
confidence: 56%
“…However, in a previous study we have shown that while there is some variation between volunteers, this had limited consequences for the amount of biofilm formation. In the same study, it was also found that the use of either individual or pooled inocula resulted in comparable biofilm growth [Janus et al, 2015]. …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The participants did not perform any oral hygiene measures for at least 5 h, and they did not drink or eat in the 2 h prior to saliva donation. Stimulated saliva was collected and stored, as described previously [20]. Inocula for the biofilm model were created by mixing stimulated saliva of a single volunteer at a 1:50 ratio with fresh biofilm growth medium, as described below.…”
Section: Methodsmentioning
confidence: 99%